HELOE DESSERT: REFORMULATION OF WATER DROPLET CAKE WITH ALOE VERA, LEMON, AND HONEY - Aldian Nerryn Putri Sumardi (Jurnal Hospitality dan Manajemen Jasa, 2020)
Abstrak: Pembukuan teoretis dan praktikal ini menggambarkan pengembangan produk makanan baru melalui kerangka teori Pengembangan Produk Baru (NPD) dengan target pasar Generasi X Eropa, terutama penduduk Swiss. Setelah penilaian menyeluruh terhadap pasar, produk yang dikonsep adalah makanan penutup sehat yang berasal dari camilan tradisional Jepang, Water Droplet Cake (Mizu shingen mochi). Untuk membantu dalam mencapai produksi versi produk yang siap dipasarkan, penelitian utama yang terperinci seperti diskusi grup terfokus dan kuesioner digunakan. Sementara itu, penelitian sekunder dalam bentuk kajian literatur juga dilakukan untuk mendukung penelitian utama. Melalui ini, model NPD yang diusulkan oleh penulis akan dieksplorasi ketika produk berevolusi, sehingga menghasilkan produk terkemuka dengan standarisasi resep yang terperinci. Kata Kunci: Makanan Sehat, Pencuci Mulut Sehat, Detoksifikasi, Pengembangan Produk Baru, Generasi X, Pasar Eropa, Lemon, Madu, Aloe Vera. Abstract: This theoretical and practical assemblage illustrates the development of a new food product through the framework of New Product Development (NPD) theory. The target market is Generation X of Europe, mainly Switzerland residents. After thorough assessment of the market, the product conceptualized is a healthy dessert that is derived from a traditional Japanese street snack, Water Droplet Cake (Mizu shingen mochi), to fill the market gap. To assist in accomplishing the production of a market-ready version of the product, detailed primary research such as focus group and questionnaires were utilized, while secondary research in the shape of literatures study are also done to support the former. Through this, the NPD model proposed by the author will be explored as the product evolves, therefore resulting in an advanced product with detailed standard recipes. Keywords: Healthy food, Healthy Dessert, Detoxification, New Product Development, Generation X, Europe Market, Lemon, Honey, Aloe Vera.